Answer:
x= -2
Step-by-step explanation:
-3x+6x+3=x-1
3x-x= -1-3
2x= -4
x= -2
Answer:
![(g\circ h)(x)=-x^2-x-3](https://tex.z-dn.net/?f=%28g%5Ccirc%20h%29%28x%29%3D-x%5E2-x-3)
Step-by-step explanation:
So we have the two functions:
![g(x)=-x-3\text{ and } h(x)=x^2+x](https://tex.z-dn.net/?f=g%28x%29%3D-x-3%5Ctext%7B%20and%20%7D%20h%28x%29%3Dx%5E2%2Bx)
And we want to find:
![(g\circ h)(x)](https://tex.z-dn.net/?f=%28g%5Ccirc%20h%29%28x%29)
This is the same thing as:
![=g(h(x))](https://tex.z-dn.net/?f=%3Dg%28h%28x%29%29)
So, substitute h(x) into g(x):
![g(x)=-x-3\\g(h(x))=-(x^2+x)-3](https://tex.z-dn.net/?f=g%28x%29%3D-x-3%5C%5Cg%28h%28x%29%29%3D-%28x%5E2%2Bx%29-3)
Distribute the negative:
![g(h(x))=-x^2-x-3](https://tex.z-dn.net/?f=g%28h%28x%29%29%3D-x%5E2-x-3)
And we're done!
So:
![(g\circ h)(x)=-x^2-x-3](https://tex.z-dn.net/?f=%28g%5Ccirc%20h%29%28x%29%3D-x%5E2-x-3)
Answer:
45"
Step-by-step explanation:
(3/4 x 60 )"
=45"
10^2 + 4 * (6 + 3) - 27 ÷ (9 - 6) = 127
=100 + 4 * 9 - 27 ÷ 3
multiplication & division before addition and subtraction (order of operations rules, PEMDAS)
100 + 36 - 9= 127
136 - 9= 127
127= 127
Place a set of parentheses around (6+3) and (9-6).
Hope this helps! :)
If you begin with the basic equation of a vertical parabola: y-k=a(x-h)^2, where (h,k) is the vertex, then that equation, when the vertex is (-3,-2), is
y + 2 = a (x + 3)^2. If we solve this for y, we get
y = a(x+3)^2 - 2. Thus, eliminate answers A and D. That leaves B, since B correctly shows (x+3)^2.